A large outbreak in Argentina of type D botulism in vaccinated cattle associated with phosphorus deficiency and osteophagy - Caspe, Sergio Gaston (2026)
Bovine botulism is a lethal disease caused by Clostridium botulinum neurotoxins (BoNT). In cattle, the most frequent form of this disease in several South American countries and elsewhere is caused by BoNT type D, which has been associated with phosphorus deficiency, leading to pica and osteophagy. An outbreak of botulism occurred in a fully vaccinated 600-steer herd of cattle. The cattle were grazing on native pasture in a paddock in which several decomposing animal carcasses were found; the animals had performed osteophagy. The first 2 deaths were recorded in November 2016, and the number of fatalities increased to 84 through April of 2017. All the cases had similar clinical signs, which were consistent with botulism. The affected animals had hypophosphatemia and rear-leg weakness, ataxia, progressive flaccid paralysis of several muscles, recumbency, and death. Autopsies were performed on 3 animals; gross findings included hydropericardium, congestion of the cerebellum, and bone fragments and stones in the rumen and reticulum. Botulism was confirmed in the 3 animals by detecting BoNT type D by mouse bioassay. A large outbreak of botulism in vaccinated cattle associated with phosphorus deficiency and osteophagy has not been reported previously in Argentina, to our knowledge. Our case demonstrates that, even in vaccinated herds, rigorous carcass management is essential to reduce the risk of environmental contamination and to prevent fatal botulism outbreaks, especially in phosphorus-deficient areas. Improved reporting of similar cases is vital to refine prevention strategies and reduce the economic impact of the disease.